Interaction Between Soyabean Protein and Molybdate Ions - SINGH, R.P.; SHARMA, A.; AHLAWAT, A.; C. KUMAR, POONAM (Asian Journal of Chemistry, 2010)
The interaction between soyabean protein and molybdate ions has been studied employing transmittance measurements. In the acidic range, the stoichiometry of the combination between molybdate ion and protonated nitrogen groups of soyabean was found to be one-to-one in the pH range 5.0 to 7.0 and higher ratio at pH-values. The pH-dependent binding result has been ascribed to the existance of anionic as well as cationic species of molybdenum(VI). The effect of pH on the formation constants and free energy changes of molybdenum(VI)-soyabean system has been discussed.